Brugada Syndrome or Phenocopy? Diagnostic Challenge in Patients with Pectus Excavatum - Luciano, Kárila Scarduelli; Goldoni, Larissa Freitas Nunes; Sales, Rafaela Louise; Ronsoni, Rafael de March (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Brugada syndrome is an autosomal dominant heart disease caused by dysfunctions in the ionic channels, whose carriers present a classic electrocardiographic pattern and predisposition to malignant ventricular arrhythmias. The electrocardiogram alterations may be dynamic, spontaneous, or induced by sodium channel blocking drugs (ajmaline, procainamide, etc.). However, electrocardiographic findings that diagnose Brugada syndrome may occur even in the absence of congenital dysfunction of ionic channels, characterizing “Brugada phenocopy”, therefore the exclusion of secondary causes is fundamental for the correct diagnosis of channelopathy.